Is there space for an industry focused research in academia? II. An industry point of view - Rodríguez Fernández de Henestrosa, Antonio (Spanish Journal of Environmental Mutagenesis and Genomics, 2023)
Academia and Industry are more and more looking for a space where both sectors can converge, thus creating important synergies that could let them to achieve their goals in a more efficient manner. In this direction, a key point for setting these collaborations up is to identify which are the needs of each part in order to bring their collaboration to a successful interaction. In this session we would highlight which are the key topics that industry is seeking in academia groups to advance in their research lines, in the field of genotoxicity assessment. New techniques, the improvement of the already existing ones or new projects seems to be potential points of collaboration. The large experience of academia in basic research and the know-how generated as a consequence of such experience is clearly an added value that the private sector should take profit of. Examples of how academia has contributed in this direction to the genotoxicity area in the last years will be presented and potential topics where industry could take profit of collaboration with academia will be suggested.